THE FLOUTED OF MAXIMS AT CARTOON MOVIE ENTITLED ‘MONSTER UNIVERSITY’ - ADELIA, FANIA RATNA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Flouting maxim, Character, Monster University The study deals with the flouting of maxims in the cartoon movie with title ‘Monster University’. There are two problems of the study, namely: (1) What maxims are flouted by the character in Monster University movie, and (2) What is the implied meaning of flouted maxim in the character’s utterance in Monster University. The objectives are to find out the utterances flouted by the characters in Monster University movie and to describe the implied meaning of flouted maxim in the character’s utterance in Monster University.The writer used two theories to conduct the analysis. First, Grice’s theory for main theory and Cutting’s theory for supporting theory for analysis. Qualitative approach in data analysis containing the flouting of maxims. The data were in the form of utterancess was used by the characters in Monster University movie.Results of this study showed there were 39 utterances which flouted the maxims, 12 utterances which flouted maxim of quantity, 8 utterances which flouted maxim of quality, 12 utterances which flouted maxim of relevance, and 7 utterances which flouted maxim of manner. The character flouted maxim of quantity and relevance the most, because they like to give too little or too short information, so if they give short information sometime they make no relation between their utterances. The reason they break the rules is in order to make natural utterances and also to supporttheir situation.The writer suggests further researchers to seek different subject of the research, such as advertisement, a comic, a song lyric and in any kinds of media to make variation in analysis. The writer also suggests that the next researcher can use more recent theory to make deeper analysis.